Review of J. Hautsch’s book “Mind, Body, and Emotion in the Reception and Creation Practices of Fan Communities: Thinking Through Feels” - Olesya S. Yakushenkova (Corpus Mundi)
The review is dedicated to J. Hautsch’s book “Mind, Body, and Emotion in the Reception and Creation Practices of Fan Communities: Thinking Through Feels,” in which the author analyses fan reading and emotional experience through various aspects of embodiment and collective interaction. The author defines the boundaries of academic understanding of emotions, emphasising their connection to bodily perception and material context. The book describes key elements of fan experience: the influence of emotions on the perception of the material, the role of body in the emotional experience of the reader, as well as the impact of actor/character and casting on interpretation. The context is also examined as a dynamic system in which fans shape and reinterpret texts within their communities, creating a collective discourse. Furthermore, the author highlights how the collaborative creation of character images by fans influences their identity formation and perception. It is emphasised that the fan experience is not solely individual, but involves active interaction with texts and each other, fostering a sense of community and interconnectedness within fan communities.